2016
DOI: 10.1186/s12864-016-2364-4
|View full text |Cite
|
Sign up to set email alerts
|

Pangenome-wide and molecular evolution analyses of the Pseudomonas aeruginosa species

Abstract: Background: Drug treatments and vaccine designs against the opportunistic human pathogen Pseudomonas aeruginosa have multiple issues, all associated with the diverse genetic traits present in this pathogen, ranging from multi-drug resistant genes to the molecular machinery for the biosynthesis of biofilms. Several candidate vaccines against P. aeruginosa have been developed, which target the outer membrane proteins; however, major issues arise when attempting to establish complete protection against this patho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 54 publications
(75 reference statements)
5
52
0
Order By: Relevance
“…This extensive diversity results in variable metabolic capacity [67], potentially supplementing individual strains with additional ecological range and providing even more opportunities for genetic exchange. Direct comparison of population structures are difficult due to different sampling and analysis strategies [66]; nonetheless it is clear that the other Gram negative opportunists also have many deep branching lineages and large pan--genomes [9,[68][69][70][71]. Coding capacity and genome size are easy to compare using public genome data (Fig 2C): K. pneumoniae has a significantly larger genome than the other Enterobacteriaceae species considered here (mean 5.7 Mbp, 5455 protein coding genes, vs 5.1 Mbp/4915 genes in E. coli and 5.0 Mbp/4680 genes in E. cloacae; p<1x10 --15 using two--sided t--test), which may help equip K. pneumoniae for survival in a broader range of niches.…”
Section: Ecological Rangementioning
confidence: 99%
“…This extensive diversity results in variable metabolic capacity [67], potentially supplementing individual strains with additional ecological range and providing even more opportunities for genetic exchange. Direct comparison of population structures are difficult due to different sampling and analysis strategies [66]; nonetheless it is clear that the other Gram negative opportunists also have many deep branching lineages and large pan--genomes [9,[68][69][70][71]. Coding capacity and genome size are easy to compare using public genome data (Fig 2C): K. pneumoniae has a significantly larger genome than the other Enterobacteriaceae species considered here (mean 5.7 Mbp, 5455 protein coding genes, vs 5.1 Mbp/4915 genes in E. coli and 5.0 Mbp/4680 genes in E. cloacae; p<1x10 --15 using two--sided t--test), which may help equip K. pneumoniae for survival in a broader range of niches.…”
Section: Ecological Rangementioning
confidence: 99%
“…Additionally, P. aeruginosa is a broad-host range opportunistic pathogen, infecting plants, invertebrates, and animals (including humans), and is implicated in a wide range of clinical infections including otitis media, wound infections, and acute and chronic pneumonias [3, 4]. Seminal genomics analyses over the past decade attribute P. aeruginosa’s capabilities to a relatively large genome (mean size of 6.6 Mbp [5]), containing an average of 6175 genes per isolate [6], as well as its disproportionately large number of regulatory elements, comprising approximately 10 % of an isolate’s genes [5]. More recently, several medium- and large-scale P. aeruginosa genomics studies (< 20, and > 100 genomes, respectively) [611] have provided a more nuanced view of the genetic capacity of the species.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal genomics analyses over the past decade attribute P. aeruginosa’s capabilities to a relatively large genome (mean size of 6.6 Mbp [5]), containing an average of 6175 genes per isolate [6], as well as its disproportionately large number of regulatory elements, comprising approximately 10 % of an isolate’s genes [5]. More recently, several medium- and large-scale P. aeruginosa genomics studies (< 20, and > 100 genomes, respectively) [611] have provided a more nuanced view of the genetic capacity of the species. In one of the largest studies to-date, Mosquera-Rendon and colleagues analyzed 181 genomes, and identified 16,820 non-redundant genes, constituting the predicted P. aeruginosa pan-genome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations